Analysis of residual stress distribution characteristics of laser surface hardening based on Voronoi model. (December 2022) - Han, Xing; Li, Chang; Liu, Zhaotai; Chen, Xinxue; Deng, Shuangjiu
Highlights: A random polycrystalline model of the matrix is established, based on the Voronoi method. The grain heterogeneity is introduced according to the nanoindentation results, and the various grain attributes are randomly assigned to the Voronoi cell by a Python script. A thermo-mechanical coupling model for the laser quenching process of SUS301L-HT stainless steel considering grain heterogeneity was established. The BOX-Behnen Design method was used to establish a response surface model, and the response surface method was combined with the Monte Carlo sampling calculation method to calculate the sensitivity of the process parameters. Abstract: The laser surface hardening's parameters have a direct effect on the residual stress of the matrix. It is important to quantitatively reveal the influence degree of process parameters on the matrix residual stress for the formulation of optimal process. In this paper, a random polycrystalline model of the matrix is established based on the Voronoi method. The grain heterogeneity is introduced according to the nanoindentation results. The divided 7 different grain attributes are randomly assigned to each voronoi cell through a python script. A thermo-mechanical coupling model for the laser quenching process of SUS301L-HT stainless steel considering grain heterogeneity was established. The thermal stress field and temperature field distribution of the single laser surface hardening are calculated with different process parameters. On this basis, the BOX-Behnen Design method was used to establish a response surface model, and the response surface method was combined with the Monte Carlo sampling calculation method to calculate the sensitivity of the process parameters. The calculation results show that the analysis value D of the residual stress is a normally distributed. Laser power and laser scanning speed are the main factors affecting the average residual stress of the grain, and the effects of the two are opposite. The laser scanning speed has a greater influence on the residual stress of the matrix than the laser power.